Overexpression of OsDUF868.12 enhances salt tolerance in rice - Hao Chen; Jiale Wan; Jiali Zhu; Ziyi Wang; Caiyao Mao; Wanjing Xu; Juan Yang; Yijuan Kong; Xiaofei Zan; Rongjun Chen; Jianqing Zhu; Zhengjun Xu; et al. (Frontiers in Plant Science)
Excessive salt accumuln in soil is one of the most important abiotic stresses in agricultural environments. The Domain of Unknown Function 868 (DUF868) family, comprising 15 members in rice, has been identified in the protein family database. In this study, we cloned and functionally characterized OsDUF868.12, a member of the OsDUF868 family, to elucidate its role in rice response to salt stress. A series of experiments, including RT-qPCR, Agrobacterium-mediated transient transformation in tobacco for localization analysis, phenotypic characterization, physiological and biochemical index measurement, and leaf staining, were conducted to investigate the function of OsDUF868.12 under salt stress. Transcriptional analysis revealed that OsDUF868.12 exhibited the most significant response to low temperature and salt stress. Preliminary subcellular localization studies indicated that OsDUF868.12 is localized in the cell membrane. Phenotypic Identification Experiments showed Overexpression lines of OsDUF868.12 enhanced resistance to salt stress and increased survival rates, while knockout lines of OsDUF868.12 were opposite. Physiological and biochemical assessments, along with leaf staining, demonstrated that overexpression of OsDUF868.12 improved the activity against oxidative stress.under salt stress. Furthermore, overexpression of OsDUF868.12 elevated the transcription levels of positively regulated salt stress-related genes. These findings suggest that overexpression of OsDUF868.12 enhances rice tolerance to salt stress at the molecular level through a series of regulatory mechanisms. This study provides valuable insights into the functional roles of the DUF868 family in plant responses to abiotic stress.